Role of cationic gemini surfactants (m-s-m type) on the oxidation of d-glucose by permanganate - Al-Thabaiti, S.A.; Obaid, A.Y.; Khan, Z.; Al-Thubaiti, K.S.; Nabi, A.; Malik, M.A. (Elsevier, 2016)
Cationic gemini (m-s-m type; m = 16, s = 4,5,6) surfactants were used to determine the micelles assisted kinetics parameters, mechanism of permanganate-D-glucose redox system in an aqueous solution by means of UV-visible spectroscopy at 40 °C. Effects of different [gemini surfactant], [permanganate], [D-glucose] and temperature on the reaction rate were investigated. Various activation parameters such as activation energy (Ea), enthalpy of activation (ΔH#), free energy of activation (ΔG#), and entropy of activation (ΔS#) have been evaluated. Menger-Portony pseudo-phase model modified by Bunton was used to analyze the role of gemini surfactant on the rate constant. Spacer chain length of surfactants has significant impact on the oxidation -reduction kinetics. A suitable mechanism reliable with the experimental results has been proposed and discussed. The cationic gemini surfactant micellar media are relatively more efficient than conventional monomeric surfactant i.e. cetyltrimethylammonium bromide (CTAB).